A new genus and new species of family Antedonidae (Echinodermata: Crinoidea) from southern Japan - Obuchi, Masami; Omori, Akihito (Zootaxa, 2015)
A new genus and new species of antedonid comatulid is described from southern Japan. Belonometra n. gen. has a unique appearance with ten long arms, numerous cirri, and remarkably long and crowded pinnules. The new genus shares some characters with subfamily Heliometrinae. However, the comparative length of pinnules, which is a diagnostic character to determine subfamily Antedonidae, is different. The subfamily into which the new genus should be placed is unclear.